2022
DOI: 10.1149/2162-8777/ac9334
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Structural, Optical and Electrical Properties of Polyaniline/Ferrite (Co, Ni, Cu, Zn) Composites

Abstract: Considering the magnificent optical and electric properties of polyaniline (PANI), in this study, PANI, PANI/MFe2O4 (M = Co, Ni, Cu, and Zn) composites were studied. Polyaniline and their composites with ferrites were prepared via chemical oxidation method. Ferrites were synthesized through co-precipitation method. Structural properties were investigated using X-Ray diffraction (XRD) and Fourier Transform Infrared spectroscopy (FTIR) respectively. Their results reveal the semi-crystalline nature of synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…37 Recently, much research has been conducted to explore the properties of Ni-Cu-Zn ferrite and develop its applications as a new nanocomposite. [38][39][40][41][42] The use of carbon nanomaterial composites such as graphene oxide, reduced graphene oxide, carbon nanotubes composites in the recent years have attracted much attention in electrode modication processes due to their suitable properties such as high surface area, conductivity and stability. Also, decrease of the required overpotential of the electrochemical reactions is one of the catalytic properties of hybrids of carbon nanomaterials.…”
Section: Omeprazolementioning
confidence: 99%
See 1 more Smart Citation
“…37 Recently, much research has been conducted to explore the properties of Ni-Cu-Zn ferrite and develop its applications as a new nanocomposite. [38][39][40][41][42] The use of carbon nanomaterial composites such as graphene oxide, reduced graphene oxide, carbon nanotubes composites in the recent years have attracted much attention in electrode modication processes due to their suitable properties such as high surface area, conductivity and stability. Also, decrease of the required overpotential of the electrochemical reactions is one of the catalytic properties of hybrids of carbon nanomaterials.…”
Section: Omeprazolementioning
confidence: 99%
“…37 Recently, much research has been conducted to explore the properties of Ni–Cu–Zn ferrite and develop its applications as a new nanocomposite. 38–42…”
Section: Introductionmentioning
confidence: 99%
“…The XRD pattern is seen in Figure 3, with peaks due to ferrites and polyaniline. The peaks less than 1000 cm −1 are due to ferrites, which occur at 512 cm −1 and 591 cm −1 and are attributed to the vibrations of metal ion and oxygen bonding at octahedral and tetrahedral sites, respectively, in the spinel structure [31], and FTIR peaks due to polyaniline are explained in Table 1 [32]. In the composites, the wavenumbers shift slightly to lower wavenumbers in the higher percentages of ferrites, which is attributed to the interaction of ferrites with polymer chains [33].…”
Section: Ftir Analysismentioning
confidence: 99%
“…Patil et al 14 reported the electric behavior of PANI/ ZnFe 2 O 4 and found that 30 wt% of ZnFe 2 O 4 in the polymer matrix exhibited an enhancement in the conductivity of the polyaniline and their values are found to be in the semiconducting range. PANI, PANI/MFe 2 O 4 (M = Co, Ni, Cu, and Zn) composites were studied by Swati Sehrawat et al 15 According to their findings, the addition of ferrite particles increased the electrical conductivity of pure PANI. The electrical conductivity of pure PANI was found to be 3 Â 10 À4 S cm À1 , while for PANI-zinc ferrite composite was found to be 5 Â 10 À4 S cm À1 .…”
Section: Introductionmentioning
confidence: 99%
“…PANI, PANI/MFe 2 O 4 (M = Co, Ni, Cu, and Zn) composites were studied by Swati Sehrawat et al 15 According to their findings, the addition of ferrite particles increased the electrical conductivity of pure PANI. The electrical conductivity of pure PANI was found to be 3 × 10 −4 S cm −1 , while for PANI‐zinc ferrite composite was found to be 5 × 10 −4 S cm −1 .…”
Section: Introductionmentioning
confidence: 99%